Models in Microeconomic Theory ('She' Edition) - Martin J. Osborne; Ariel Rubinstein (Open Book Publishers, 2020)
"Models in Microeconomic Theory covers basic models in current microeconomic theory. Part I (Chapters 1-7) presents models of an economic agent, discussing abstract models of preferences, choice, and decision making under uncertainty, before turning to models of the consumer, the producer, and monopoly. Part II (Chapters 8-14) introduces the concept of equilibrium, beginning, unconventionally, with the models of the jungle and an economy with indivisible goods, and continuing with models of an exchange economy, equilibrium with rational expectations, and an economy with asymmetric information. Part III (Chapters 15-16) provides an introduction to game theory, covering strategic and extensive games and the concepts of Nash equilibrium and subgame perfect equilibrium. Part IV (Chapters 17-20) gives a taste of the topics of mechanism design, matching, the axiomatic analysis of economic systems, and social choice. The book focuses on the concepts of model and equilibrium. It states models and results precisely, and provides proofs for all results. It uses only elementary mathematics (with almost no calculus), although many of the proofs involve sustained logical arguments. It includes about 150 exercises. With its formal but accessible style, this textbook is designed for undergraduate students of microeconomics at intermediate and advanced levels. "
Keywords: 330; microeconomic theory; basic models; models of an economic agent; equilibrium; game theory; mechanism design; matching; axiomatic analysis of economic systems; social choice; undergraduate students; microeconomics; microeconomic theory; basic models; models of an economic agent; equilibrium; game theory; mechanism design; matching; axiomatic analysis of economic systems; social choice; undergraduate students; microeconomics